Istirātījiyyāt Ta - Suci Ramadhanti Febriani; Wahyuni Wahyuni; Muhamad Bisri Ihwan; Wildana Wargadinata (Universitas Islam Negeri Palangka Raya, 2020)
One of the most important aspects of learning is the